The brazilian hazard-based cut-off criteria for pesticide registration: a critical appraisal - Francisco JosÃ© Roma Paumgartten (Fundação Oswaldo Cruz (FIOCRUZ), 2012)
Brazil, worldâ€™s top consumer of agricultural pesticides, adopts a unique hazard based cut-off approach to pesticide registration. Cut-off criteria for mutagenicity, carcinogenicity, teratogenicity, hormonal disturbances and damage to reproductive organs were introduced by the Pesticide Law enacted in 1989. As far as health is concerned, law enforcement is additionally regulated by rules issued by the federal health authority (National Agency for Health Surveillance â€" ANVISA). Contrasting to European Union hazard-based cut-off criteria for pesticides, Brazilian rules do not make an exception for â€œnegligibleâ€ exposures. Moreover, Brazilian regulations have shortcomings (e.g. no reference to relevance of Mode of Action to humans) that make cut-off criteria difficult to be put into effect. The deficiencies of regulations and difficulties to consistently apply the hazard-based cut-off criteria are appraised in this article. Adoption of a risk assessment approach or cut-off criteria based on classification in Globally Harmonized System hazard categories 1A and 1B is suggested.